An Error-resilient Image Coding and Packetization Scheme for Packet-switched Networks - Jianming Wei; Salari, E. (2006 IEEE International Conference on Electro/Information Technology, 2006)
An error-resilient image coding and fixed-length packetization scheme is presented to prevent packet loss from packet-switched networks. A wavelet coder based on set partition in hierarchy trees (SPIHT) algorithm encodes the wavelet coefficients into an embedded bitstream along with markers generated to record the order of bits within the bitstream. A fixed-length packetization scheme based on the error-resilient entropy code (EREC) is proposed to pack the encoded bitstream into fixed-length packets which can be transmitted over the physical packet-switched network. Any lost packets only have minor effects on other received packets. Computer simulations show that our proposed method provides both excellent compression performance with fast speed and graceful degradation under various packet erasure rates (PER)